Lion population status and ecology in a seasonally-flooded wetland, the Okavango Delta - Kotze, Christen Robynne (Department of Biological Sciences, 2023)
The Okavango Delta in north-western Botswana, is a population stronghold for the African lion (Panthera leo). As lion populations are declining, there is a pressing need to develop conservation plans that can secure the future for lion populations in natural environments that face increasing anthropogenic pressure. The Okavango Delta is a dynamic wetland that undergoes significant ecological change in response to an annual flood pulse, the extent of which is determined by both short-and long-term climatic variation. The resulting fluctuations in landscape structure and resource availability affect all trophic levels. However, their effects on apex predators are not well understood. In this thesis, I examined which ecological and anthropogenic factors underpin population processes such as population density, home range size and resource selection of lions in the Okavango at various temporal and spatial scales, in order to better inform conservation plans for this population. As lions can be difficult to count, a situation made more challenging by a seasonally flooded environment, I first looked at camera trapping as a potential survey method for lions. With high resolution images, lions could be individually identified from trap images and spatiallyexplicit capture-recapture applied to produce reliable population estimates. Furthermore, spatial variation in density could be linked to environmental and anthropogenic covariates. Lion densities were highest along the floodplains, and were correlated strongly with vegetation productivity, but decreased with proximity to human settlements, suggesting an edge effect along the boundaries of the wildlife management areas. This edge effect may result from retaliatory killing in response to livestock predation by lions in adjacent community areas but could also be the effect of prey depletion from bushmeat harvesting along the Okavango's boundaries. As flooding can induce significant changes in landscape structure, I examined what effect this had on lion home range size at minimum and maximum flood extent. When floods were at their lowest, home range sizes of males were larger than those of females, which is typical of large carnivores. Females appeared to minimize the area used by prioritizing access to prey, and home range was also negatively correlated with habitat heterogeneity and island size and connectivity. Male home range sizes, however, were not affected by prey availability, but instead were negatively correlated with habitat heterogeneity and proportion of woodland, both of which are considered indices of high-quality habitat in this landscape. As higher quality habitat may result in higher female density, males may instead be trying to maximize access to areas which would have a higher density of females. At peak flood, however, males and females had similar range sizes, and home range sizes were positively correlated with dry land fragmentation. During high flood phases, lower availability of dry land, together with the need to increase home range size as land fragments, could exacerbate intraspecific competition for space, and potentially increase conflict with adjacent communities as floods displace lions towards the boundaries of the wildlife management areas. However, in extended phases of low flood, which could result from prolonged drought, rising 2 temperatures or excessive water abstraction for human use, habitat heterogeneity may decline, with potential negative effects on herbivore and lion populations. Consequently, both scenarios are predicted to ultimately reduce the carrying capacity for resident lions. Lastly, I examined seasonal resource use at a finer scale, and focused on how changes in flooding could affect the size of population cores in the Okavango and connectivity between these, and connectivity from the Okavango to surrounding areas. Seasonal habitat selection by lions mimicked shifts exhibited by large herbivores in other studies on the Okavango, and habitat selection was therefore likely driven by seasonal prey availability. After translating resource selection into resistance maps, I found that seasonal permeability of the landscape to movement differed significantly based on the flood levels. During maximum flood, the lion population within the Okavango becomes fragmented - the population cores in the central, southern and western Delta decrease in size and become isolated from the rest of the Okavango Delta. During both seasons, lions avoided areas close to people, and as a result, connectivity from the Okavango moving outwards to the south and west was limited. Connectivity towards Chobe National Park to the east, however, remained intact. Therefore, restoring connectivity with neighbouring sub-populations to the south and to the west of the Okavango, and reducing anthropogenic pressure on lions in these regions during high flood phases, will help build resilience for the Okavango's lion population and should be considered a conservation priority. Ultimately, the consequences of low and high flood scenarios for lions can serve as a proxy for protracted periods of 'dry' and 'wet' environmental conditions that could result from climate change or upstream water extraction. This study shows that both flood extremes, in the long-term, can be detrimental to the Okavango lion population. It also provides a framework for long-term monitoring of lions in this wetland to be able to detect population changes. The future of the Okavango lion population depends largely on compensating for impacts of climate change by minimizing upstream water offtake to maintain natural flood cycles and reducing other anthropogenic pressures. The results of this study may also provide insights into conservation challenges impacting big cat populations in wetlands elsewhere around the world.